Translation, cultural adaptation and recommendations for clinical implementation of the Abbey Pain Scale to a Swedish dementia care context - Sussi Tegenborg; Per Fransson; Lisa Martinsson (Wiley, 2023)
Abstract Aim To translate and culturally adapt the APS for people with end‐stage dementia in various care settings in Sweden and to investigate factors important for clinical implementation. Design Qualitative study design with interviews with care staff. Methods After an initial discussion of concepts, the Abbey Pain Scale was translated into Swedish and back into English to check for accuracy. The resulting Swedish version was then revised and culturally adapted through a series of interviews with nursing assistants, nurses and physicians (n = 11) to develop the final Swedish version. Results A Swedish version of the Abbey Pain Scale was developed. The instrument was considered straightforward and easy to use, but needed adjustments to make it more comprehensible to staff with less education in health care or with other first languages than Swedish. It was found important to carefully introduce new staff members to the instrument, to ensure they understand all the words and items.